Strategi Komunikasi Pemasaran Kelompok Tani Rubaru dalam Meningkatkan Penjualan Bawang Merah sebagai Komoditi Unggulan Kabupaten Sumenep - Anis Kurli; Rillia Aisyah Haris; Ida Syafriyani; Raudhah Pattria Sari; Purnama Violita Putri; Rahman Riady (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Sumenep as one of the easternmost districts on Madura Island has the most promising agro-political potential. The agricultural sector is the primary source of livelihood, both on land and in some areas. According to the statistics of the Central Statistical Authority (CST) of Sumenep district in 2021 the largest contributor of Gross Regional Domestic Product (GDP) is 39.41% as the largest agropolitical producer compared to other sectors. The agricultural area of Sumenep district reached 207.010 hectares with a total production of 828.814 tons. As for the purpose of this study is how the Marketing Communication Strategy of Tani Rubaru Group in increasing the sale of red onions as a major commodity in Sumenep district. The method used in this research uses qualitative descriptive with data collection techniques were in-depth interviews and observation. The results of this research show the marketing communication strategy carried out by Tani Rubaru Group to increase the sale of Red Onion with the development of production activities, development of processing products of various variants, development and practice in marketing activities through social media